Stunting prevention and management program in Benteng Urban Village, Warudoyong Sub-District, Sukabumi City - Fina Pauzina Patmawati; Prisma Mariana Ibrahim; Ahmad Hamidi (Universitas Pendidikan Indonesia, 2024)
One of the priorities of national development is to create quality and competitive Human Resources. One of the indicators related to the creation of quality human resources is the fulfillment of targets and targets in the health sector, where one of the indicators is the decline in the prevalence of stunting in Indonesia. The 2021 SSGI survey data states that the prevalence of stunting in West Java Province is categorized as high so the West Java zero New Stunting program is targeted in 2023. As a commitment to accelerate the reduction of stunting, the Government has issued Peraturan Presiden No. 72 tahun 2021 tentang Percepatan Penurunan Stunting. Through this Important Thematic Real Work Lecture program, which is a community service program, it can be a bridge for students to be able to apply their abilities by conducting field lectures and mingling directly with the community, as agents of change. The research in this activity is a qualitative method. Data sources are obtained from various in-depth interviews and focus group discussions with program implementation at the Village level and related stakeholders. There are six activities carried out in the 2023 UPI Thematic Si Penting KKN activities in Benteng Village with the target activities being integrated health posts, adolescent integrated health posts, residents at risk of stunting, and the community. Abstrak Salah satu prioritas pembangunan nasional adalah mewujudkan Sumber Daya Manusia yang berkualitas dan berdaya saing. Adapun salah satu indikator yang terkait dengan penciptaan SDM yang berkualitas adalah terpenuhinya sasaran dan target dibidang kesehatan, dimana salah satu indikatornya adalah menurunnya angka prevalensi stunting di Indonesia. Data survei SSGI tahun 2021 yang mengatakan bahwa prevalensi stunting di Provinsi Jawa Barat dikategorikan tinggi sehingga ditargetkan program Jabar Zero New Stunting pada 2023. Sebagai salah satu komitmen untuk mempercepat penurunan stunting, Pemerintah telah menerbitkan Perpes No. 72 tahun 2021 tentang percepatan penurunan stunting. Melalui program Kuliah Kerja Nyata Tematik Si Penting ini yang merupakan program pengabdian kepada masyarakat dapat menjadi jembatan mahasiswa untuk bisa mengaplikasikan kemampuan dengan menjalankan kuliah lapangan dan berbaur langsung dengan masyarakat, sebagai agent of change. Penelitian dalam kegiatan ini ialah metode kualitatif. Sumber data diperoleh dari berbagai wawancara secara mendalam dan diskusi kelompok terfokus (focus group discussion) dengan pelaksanaan program di tingkat Kelurahan dan stakeholder terkait. Ada enam kegiatan yang dilakukan dalam kegiatan KKN Tematik Si Penting UPI Tahun 2023 di Kelurahan Benteng dengan sasaran kegiatan posyandu, posyandu remaja, warga rawan stunting, dan masyarakat. Kata Kunci: pencegahan stunting; pengabdian kepada masyarakat; program manajemen